Log Demand and Supply in Indonesia - Trisakti, Nely (Universitas Trisakti, 2006)
In the 1980s, the government issued a ban on log exports. This policy was intended to encourage domestic downstream forest-based industries and the export of processed products. Subsequently, in 1992 the government doubled the sawn wood export tax and made it impossible to export rough sawn wood. However, these policies then resulted in industrial capacities and led to unsustainable logging practices.This study aims to identify and analyze factors that influence the production and demand of logs in Indonesia, as well as to evaluate the impacts of relevant policy on the Indonesian forestry sector. For this purpose, the author uses an econometric approach with a simultaneous equation model. The parameters in the model are estimated using the 2SLS (Two Stage Least Square) method. Then a simulation analysis is employed to measure the response of the model to changes in policy instruments. The author hopes this study can give a picture of log demand and supply in Indonesia and their related policies.